Digital marketing's impact on Central Borneo consumers' propensity to buy via increased brand recognition The Regional National Crafts Council's Souvenir - Hardianti, Lusi; Kristinae, Vivy (JSM: Jurnal Sains Manajemen, 2024)
The objective of this investigation is to ascertain. The Impact of Digital Marketing on Consumer Purchasing Decisions through Brand Awareness at Central Borneo Dekrasnda Souvenirs. This research employs a quantitative methodology, utilizing a sample size of 100 respondents. The data collection in this research employed a questionnaire that utilized a Likert scale. The research utilizes primary and secondary data sources. The investigation was carried out utilizing the Partial Least Square (PLS) analysis method.The research findings indicate that Digital Marketing has a noteworthy and positive impact on Purchasing Decisions and Brand Awareness at Central Borneo Souvenir Dekranasda. Additionally, Brand Awareness also has a positive and significant influence on Purchasing Decisions at Central Borneo Souvenir Dekranasda. Furthermore, Digital Marketing has a positive and significant influence on Purchasing Decisions by means of Brand Awareness at Central Borneo Souvenir Dekranasda